HOUSE-OWNERSHIP, PSYCHOSOCIAL FACTORS AND THE MODERATING EFFECT OF NEIGHBOURHOOD ON LIFE SATISFACTION AMONG RESIDENTS IN IBADAN METROPOLIS, NIGERIA (2015)
Life satisfaction, identified as one of the important components of quality of life, is generally low in Nigeria. Most studies on life satisfaction have been focused on the effects of psychological factors to the neglect of the importance of house-ownership and neighbourhood effect. This study, therefore, investigated the influence of house-ownership, religious commitment, self-esteem, social support, personality factors and the moderating effect of neighbourhood on life satisfaction among residents in Ibadan metropolis. The Maslow’s Hierarchy of Needs theory provided the framework for this study. Using a 5-way factorial design and a multistage sampling technique, five of the eleven Local Government Areas (LGAs) in the metropolis were purposively selected. Based on the list of enumeration areas for 2005 census, 10 enumeration areas each were selected from the LGAs with simple random technique. The number of houses on the selected enumeration areas were determined with enumeration area maps. Two hundred and twenty households each were selected from the LGAs using systematic technique making a total of 1,100 houses. The selected houses were marked and the household heads were sampled. A structured questionnaire focusing on socio-demographic profile, life satisfaction scale (r=0.74), religious commitment scale (r=0.72), the big 5 personality inventory (r=0.76), self-esteem scale (r=0.61) and a multi-dimensional scale of perceived social support (r=0.87) was administered to the participants. Data were analysed using descriptive statistics, analysis of variance and multiple regression at 0.05 level of significance. The participants’ age was 42.11+15.20 years. There were 56.2% females. Participants’ educational qualification was 9.9% no formal education, 23.7% primary education, 29.9% secondary education and 36.5 tertiary education. There were 89.5% Yoruba, 5.9% Igbo, 3.4% Hausa and 1.2% other ethnic groups. Participants’ marital status was 79.6% married, 1.7% separated, 0.27% divorced, 4.9% widowed and 13.5% nevermarried. There were 42.5% Christians, 56.6% Muslims and 0.9% traditional worshippers. Respondents’ house-ownership status was 31.9% house-owners and 68.1% renters. There were 18.0% participants from the low density areas, 54.1% from the high density areas and 27.9% from the medium density areas. House-ownership, neighbourhood effects, religious commitment and social support jointly predicted life satisfaction (R2=10.0; F=24.75). House-ownership interacted with openness to predict life satisfaction (F(1,928)=4.39). Neighbourhood significantly moderated the effect of house-ownership on life satisfaction (F(2,926)=2.94). There was a significant interaction effect of religious commitment and social support on life satisfaction (F(1,237)=4.15). Conscientiousness significantly interacted with agreeableness to predict life satisfaction (F(1,686)=4.15). There was an interaction effect of neuroticism and educational qualification on life satisfaction (F(3,658)=7.24) and there was a significant interaction effect of self-esteem on gender to predict life satisfaction (F(1,685)=5.40). House-ownership was not crucial but neighbourhood was essential in improving life satisfaction. Emphasis should be placed on neighbourhood effect in improving life satisfaction